Influence of spatio temporal scales in crop water footprinting and water use management: Evidences from sugar beet production in Northern Spain. (15th December 2016) - González Perea, R.; Camacho Poyato, E.; Montesinos, P.; García Morillo, J.; Rodríguez Díaz, J.A.
Abstract: The 70% (approximately) of the total water available in the world is used by agricultural production. The crop water footprint along with irrigation management information (deficit irrigation, water need for cropping practices …) can be used as a global indicator of the water use efficiency of each crop. The spatiotemporal scale of the water footprint assessment affects the accuracy of the results, and therefore the suitability of the water footprint accounting in relation with the assessment to be done. The main goal of this paper is to carry out a joint evaluation of crop water footprint and irrigation management at field level of outdoor extensive crops such as sugar beet in Northern Spain. The water footprint for the two studied seasons showed an average value of 76.04 m 3  t −1 and 68.26 m 3  t −1 respectively. These values are significantly different to those published by other authors for sugar beet, mainly due to the different spatiotemporal scales considered. Also, the water footprint in liked to the irrigation management using the Relative Irrigation Supply (RIS) indicator. Thus, data collected at farm level are recommended for local studies and to formulate strategies to reduce water footprints and to improve on-farm water use efficiency.